Girls of tender age: a memoir - Smith, Mary-Ann Tirone (New York Free Press, 2006)
Traces the author's experiences of growing up in a small-town community under the shadows of a severely autistic brother and a violent serial pedophile who eventually murdered one of the writer's young classmates
Baker & Taylor, 1/23/2006, 13.44
Keywords: Smith,Mary-Ann Tirone -- Childhood and youth; Smith,Mary-Ann Tirone -- Homes and haunts -- Connecticut -- Hartford; Novelists -- American -- Homes and haunts -- Connecticut; Noverlists, American -- 20th Century -- Biography; Hartford (Conn.) -- Social life and customs